Aplikasi Digitalisasi Seni Bela Diri Silat Tradisional Minangkabau - Tri Lestari -; Taufik Gusman -; Defni - -; Muhammad Yosazikri Ikhsan (Jurnal Ilmiah Poli Rekayasa, 2020)
Minangkabau traditional martial arts digitization app is an android game-shaped application created to display minangkabau silat using 3-Dimensional (3D) animation technology. This app will convert materials and illustrations into 3D animated shapes that can be played using the android app so that it will attract users to more easily understand and understand about minangkabau silat. The data that is made as a necessity for application is obtained from literature studies and field studies by using interview techniques with silat officials in Padang city. For the creation of this game application using virtual reality technology and the tools used are 3 Dimensional blender and Unity Game Engine.